Lattice-strain effect on oxygen vacancy formation in gadolinium-doped ceria - Ahn, Kiyong; Chung, Yong-Chae; Yoon, Kyung Joong; Son, Ji-Won; Kim, Byung-Kook; Lee, Hae-Weon; Lee, Jong-Ho (SPRINGER, 2014)
By first-principles calculations using the projector-augmented-wave (PAW) method, the oxygen vacancy formation energy of gadolinium-doped ceria (GDC) is calculated as a function of lattice strain comprising the range from compressive (-1.5 %) to dilative (1.5 %) strain. Employing the generalized gradient approximation (GGA) for the exchange correlation potential and including the strong on-site Coulombic repulsion U, the calculations are performed within the (GGA) + U formalism. For simplicity of interpretation, all calculations are carried out based on the assumption that structural relaxation in GDC occurred under isotropic strain states. According to the calculation of the energetics of vacancy formation, the formation energy shows the lowest value at dilative strain conditions, where the lattice structure is in the loosest state. Furthermore, the generated oxygen vacancy has a preferred migration path that is mainly controlled by the neighboring cation configuration.
Keywords: YTTRIA-STABILIZED ZIRCONIA; IONIC-CONDUCTIVITY; ELECTRICAL-PROPERTIES; ELECTROCHEMICAL PROPERTIES; FILMS; OXIDE; CEO2; 1ST-PRINCIPLES; ELECTROLYTES; SIMULATION